Dimensionality changes actin network through lamin A/C and zyxin. (May 2020) - Zonderland, Jip; Moldero, Ivan Lorenzo; Anand, Shivesh; Mota, Carlos; Moroni, Lorenzo
Abstract: Mechanosensing proteins have mainly been investigated in 2D culture platforms, while understanding their regulation in 3D enviroments is critical for tissue engineering. Among mechanosensing proteins, the actin cytoskeleton plays a key role in human mesenchymal stromal cells (hMSCs) activity, but its regulation in 3D tissue engineered scaffolds remains poorly studied. Here, we show that human mesenchymal stromal cells (hMSCs) cultured on 3D electrospun scaffolds made of a stiff material do not form actin stress fibers, contrary to hMSCs on 2D films of the same material. On 3D electrospun and additive manufactured scaffolds, hMSCs also displayed fewer focal adhesions, lower lamin A and C expression and less YAP1 nuclear localization and myosin light chain phosphorylation. Together, this strongly suggests that dimensionality prevents the build-up of cellular tension, even on stiff materials. Knock down of either lamin A and C or zyxin resulted in fewer stress fibers in the cell center. Zyxin knock down reduced lamin A and C expression, but not vice versa, showing that this signal chain starts from the outside of the cell. Lineage commitment was not affected by the lack of these important osteogenic proteins in 3D, as all cells committed to osteogenesis in bi-potential medium. Our study demonstrates that dimensionality changes the actin cytoskeleton through lamin A and C and zyxin, and highlights the difference in the regulation of lineage commitment in 3D enviroments. Together, these results can have important implications for future scaffold design for both stiff- and soft tissue engineering constructs.